Factors that influence retirement saving behavior among employees: case study at Majlis Bandaraya Melaka Bersejarah / Nur Husnina Omar and Muhamad Faiz Mansor - Omar, Nur Husnina; Mansor, Muhamad Faiz (Faculty of Business and Management, 2014)
This report is attempted to know what is the most factors that influence retirement saving behaviour among employees in Majlis Bandaraya Melaka Bersejarah (MBMB). Background and current issues in MBMB was highlighted in order to give a better understanding on what was happen. The research was focus on retirement saving behaviour among MBMB’s employees and what were the most factors will influence them. Further, the research will know whether the financial risk, goal clarity or financial literacy that having the relationship to the retirement saving behaviour. The method use in this research is via questionnaire than been administered to employees in MBMB based on the convience sampling (non probability sampling). The employees come from this organization itself. Several mechanisms also have been suggested by the researcher in order to ensure that the saving behaviour can be maintained and benefited to the employees.